Nature and origin of anorthosite enclaves within Proterozoic granite of Chotanagpur Granite Gneiss Complex of Eastern India - Negi, Priyanka; Saikia, Ashima; Ahmad, Mansoor; Upadhyay, Dewashis; Akhtar, Salim (Frontiers in Earth Science, 2022)
The Central Indian Tectonic Zone (CITZ) is a Proterozoic suture along which the Northern and Southern Indian Blocks are inferred to have amalgamated, forming the Greater Indian Landmass. The Chotanagpur Granite Gneissic Complex (CGGC) represents the eastern extension of the CITZ and exposes several granitic plutons. Enclaves of diverse origin are present as minor constituents within these granitic bodies. This study reports new major and trace element data for anorthosite enclaves hosted within granites in the Pattharkatti and Rajgir area from the northern margin of CGGC to get modern insights into the petrogenesis of anorthosites. Anorthosite enclaves show sharp contact with the host granite. They contain cumulus plagioclase (An87-94), intercumulus amphibole (magnesio-hornblende and ferro-tschermakite) and biotite (Mg-biotite and phlogopite) along with minor iron oxides. Amphibole crystallisation pressure and temperature is constrained between 3.2 - 6.4 kbar and 653 – 780 °C for the anorthosites. The studied anorthosites display a very gradual and steady increase in whole rock rare earth element (REE) contents from Lu to La [(La/Yb)N = 1.22 - 13.08]. They also show a sharp decline in Fe2O3(t) and MgO, while Al2O3 increases sharply with increasing silica contents from 45.69 to 51.16 wt.%. In chondrite normalized REE diagram, plagioclase exhibit LREE enriched patterns (La/Yb)CN = 23.34 - 422.79) with strong positive Eu anomalies. The composition of parental liquid for anorthosite from the study area were estimated by adopting the equilibrium distribution method. Parental melt curves from Sm to La are near-parallel and constrained broadly between trapped melt fractions (TMF) = ~5 - 15%. Anorthosites of the study area may have formed from water-saturated, super-heated plagioclase-saturated basaltic melt.